2012
DOI: 10.1063/1.4705305
|View full text |Cite
|
Sign up to set email alerts
|

A permendur-piezoelectric multiferroic composite for low-noise ultrasensitive magnetic field sensors

Abstract: Low-frequency and resonance magnetoelectric (ME) effects have been studied for a trilayer of permendur (alloy of Fe-Co-V) and lead zirconate titanate (PZT). The high permeability and high magnetostriction for permendur, key ingredients for magnetic field confinement, and ME response result in ME voltage coefficient of 23 V/cm Oe at low-frequency and 250 V/cm Oe at electromechanical resonance (EMR) for a sample with PZT fibers and inter-digital-electrodes. Theoretical ME coefficients are in agreement with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…This strain is coupled into the PE layer via the bonding layer. Many enhancements have been carried out choosing the material and adjusting the ratio between the MS and PE phases of the composite [3]- [6]. Thereafter, noise sources in the laminate have been investigated to evaluate the expected noise performance for magnetic sensor applications.…”
Section: Introductionmentioning
confidence: 99%
“…This strain is coupled into the PE layer via the bonding layer. Many enhancements have been carried out choosing the material and adjusting the ratio between the MS and PE phases of the composite [3]- [6]. Thereafter, noise sources in the laminate have been investigated to evaluate the expected noise performance for magnetic sensor applications.…”
Section: Introductionmentioning
confidence: 99%
“…11 Permendur (P), an alloy with 49% Fe, 49% Co, and 2% V (obtained from the Institute of Technical Acoustics, Vitebsk, Belarus), with high magnetostriction (k % 70 ppm) and high piezomagnetic coefficient (q % 1 Â 10 À6 /Oe) was used for the ferromagnetic phase in the composites. 12 Permendur of similar lateral dimensions as LGT and 0.16 mm in thickness were used in LGT-P bilayers and P-LGT-P trilayers. Platelets of P and LGT were bonded with a 2 lm thick epoxy that was cured at 40 C. We also prepared similar bilayers and trilayers of P and 25 Thus the thickness fraction of ferromagnetic and ferroelectric (or piezoelectric) layers for the 3 samples is approximately equal, although PMN-PT could only be obtained with a maximum length of 20 mm.…”
mentioning
confidence: 99%
“…1 The combination of such magnetostrictive materials with piezoelectric phases enables the formation of magnetoelectric (ME) composites exhibiting a high potential for magnetic sensing applications due to their limits of detection in the pT/ͱHz range. 2,3 The highest sensitivities are obtained in presence of externally applied magnetic bias fields, 4 which may cause unwanted perturbation to adjacent sensors and results in lower spatial resolution of sensor arrays. Recently, we demonstrated that this drawback can be overcome via the successful integration of bias fields with the exchange bias (EB) effect.…”
mentioning
confidence: 99%